Hydrogen-induced fuel system in RCCI engine for clean combustion: A review - Eswanto, .; Mohd Adnin, Hamidi; Wan Muhammad Noor Sarbani, Mat Daud; Ahmad Fitri, Yusop; Kifli, Umar; Iwan, Gunawan (Universitas Muhammadiyah Magelang, 2025)
Research in the field of internal combustion enigine using environmentally friendly fuels must be the main focus to increase efficiency, engine performance, reduction of exhaust gas emissions to clean combustion. Reactivity Controlled Compression Ignition (RCCI) on the diesel engines can be used as an innovative solution to increase thermal efficiency and reduce emissions through bending of fuels with different reactivity. This paper presents a comprehensive review of hydrogen-induced fuels systems on RCCI engines, as well as its impact on engine performance, emissions to Clean Combustion. Various studies show that mixing hydrogen in RCCI engines can increase thermal efficiency, speed up the combustion process, and reduce nitrogen oxides (NOx), particulate metter (PM), carbon monoxide (CO), hydrocarbons (HC) and Smoke Opacity emissions. This review provides insight into the trend of development of hydrogen-induced RCCI on diesel engines and its prospects in realizing a clean and efficient combustion system, so that future research focus is important for finding appropriate fuel mixtures, operating parameters, and choosing optimal engines by considering technical problems, thermodynamics, economics, and the environment, as well as exploring the potential implementation of this technology in the future.